2020
DOI: 10.1136/bmjdrc-2019-000850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors and risk of type 2 diabetes among women with a history of gestational diabetes: findings from two independent populations

Abstract: ObjectiveWomen with a history of gestational diabetes mellitus (GDM) have an exceptionally high risk for type 2 diabetes (T2D). Yet, little is known about genetic determinants for T2D in this population. We examined the association of a genetic risk score (GRS) with risk of T2D in two independent populations of women with a history of GDM and how this association might be modified by non-genetic determinants for T2D.Research design and methodsThis cohort study included 2434 white women with a history of GDM fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
2
32
2
2
Order By: Relevance
“…This finding persists after adjustment for established clinical risk factors and the QDiabetes risk score. Our findings are in keeping with prior reports of an association between a type 2 diabetes-PRS and development of type 2 diabetes in white (18) and South-East Asian (19) women with a history of GDM. While previous studies have applied alternative type 2 diabetes-PRSs to women of South Asian origin to identify those at higher risk of GDM(39), none to date have explored their association with type 2 diabetes development in women with GDM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding persists after adjustment for established clinical risk factors and the QDiabetes risk score. Our findings are in keeping with prior reports of an association between a type 2 diabetes-PRS and development of type 2 diabetes in white (18) and South-East Asian (19) women with a history of GDM. While previous studies have applied alternative type 2 diabetes-PRSs to women of South Asian origin to identify those at higher risk of GDM(39), none to date have explored their association with type 2 diabetes development in women with GDM.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, we tested whether the PRS enhances the prediction of incident type 2 diabetes when integrated with the commonly-used clinical risk score, QDiabetes (17). Thirdly, we sought to investigate whether the PRS alone might predict the progression to type 2 diabetes from gestational diabetes in BPB women, as has been observed in European and South-East Asian populations (18,19). Finally, we explored whether the PRS might predict clinically heterogeneous type 2 diabetes subgroups at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-genetic environmental factors related to development of type 2 diabetes such as diet, exercise and socioeconomic deprivation remain a key consideration, as genetics will explain only a portion of risk for type 2 diabetes in women with a history of GDM. For example, a recent study of 2,434 women of white ethnicity found that ~26% women with a history of GDM and a type 2 diabetes genetic risk score in the highest quartile had developed diabetes at follow-up compared with ~23% of women in the lowest genetic risk score quartile 16 . The GSs in this study were not analysed for their association with incident T2D in the HAPO Follow-Up Study, but this would be useful to establish and make direct comparisons with the results of this work in the future…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether lifestyle interventions such as guided diet and exercise programmes could modify risk of progressing to type 2 diabetes in women with a history of GDM and a high genetic risk. A study of 1,744 white women suggested that risk of developing type 2 diabetes after a pregnancy affected by GDM was greatest in women with a high genetic risk score and poor diet 16 . On the other hand, while the Diabetes Prevention Program (DPP) 50 trial found that lifestyle intervention or metformin treatment reduced risk of progression to type 2 diabetes in women with impaired glucose tolerance and a history of GDM (according to relevant criteria at time of diagnosis), a genetic risk score for type 2 diabetes did not influence treatment response 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation